Zinc Level and Its Role in Recurrent Infection: A Case Report and Literature Review - Swetha Parvataneni MD; Avinash R. Dasari MD (SAGE Publishing, 2020)
Clostridium difficile infection is a common nosocomial infection in US hospitals, accounting for approximately 12 800 deaths annually in the United States. These infections are often associated with the use of antibiotics, which can alter the gut microbiome and thus render patients susceptible to C difficile infection. C difficile is often spread via fecal oral transmission. Multiple medications have been developed, but recurrence rates reach 60% after treatment. Recent data have shown that zinc supplementation decreases the recurrence of C difficile infection. In this article, we present a case of recurrent C difficile infection with zinc deficiency in which zinc supplementation improved the symptoms and reduced the incidence of recurrence.